A Question of Leadership Are Western Leadership Development Approaches Appropriate in China, or Might a Chinese Approach Be More Effective - Weldon, Elizabeth; Weldon, Elizabeth; Chow, Maria (Center for Creative Leadership, 2005)
Western companies continue to invest in China, with many companies integrating their Chinese operations into their global strategies. These organizations, along with Chinese companies-- whether private or state-owned--all need more-effective leaders.